CHARACTERIZING THE HUMAN INTESTINAL MICROBIOTA IN HEALTHY INDIVIDUALS AND PATIENTS WITH ULCERATIVE COLITIS USING CULTURE-DEPENDENT AND -INDEPENDENT APPROACHES - Shekarriz, Shahrokh (My University, 2022)
The collection of microbes that inhabits the human gastrointestinal tract is known as intestinal microbiota, and an enormous body of work has shown that their activities contribute to health and disease. Ulcerative colitis (UC), which is a type of inflammatory bowel disease, is considered to arise due to a disruption in the balance between the immune system and microbiota. However, there is little consensus on the mechanism of action and microbes involved in the disease manifestation. In this work, I applied culture-enriched metagenomics (CEMG) to characterize the dynamics of gut microbiota in healthy individuals and UC patients. I showed that CEMG provides a higher resolution to study these microbial communities, and we used this approach to understand microbial colonization after fecal microbiota transplantation (FMT) therapy in UC patient. I showed that sequencing approaches alone did not reveal consistent engraftment across FMT responders. Using CEMG and a collection of bacterial whole-genome sequences, I showed patient-specific microbial strain transfer and a signature of commonly engrafted genes only in patients who responded to FMT. In this work, I also investigated the dynamics of a highly abundant bacteriophage, crAssphage, in an FMT donor and implemented a new method to detect bacteriophage engraftment post-FMT using SNP analysis. Finally, it has been suggested that antibiotic treatment before FMT may increase the efficacy of FMT. However, in this work, I show that while antibiotics alter the microbiome, there was no difference in the composition of the microbiome of antibiotic vs placebo group post-FMT. This is consistent with the randomized controlled trial results that shows pretreatment with antibiotics does not improve FMT outcome. Together, this work demonstrate the importance of in-depth microbiome analysis applied to culture-dependent and -independent sequencing to characterize microbial changes post-FMT.
CHARACTERIZING THE HUMAN INTESTINAL MICROBIOME
Keywords: Gut microbiome; Intestinal Microbiota; Microbiota; ulcerative colitis